Seatone in rheumatoid arthritis: a six-month placebo-controlled study. Issue 3 (March 1985) - Larkin, J G; Capell, H A; Sturrock, R D
Abstract : Thirty-five patients with rheumatoid arthritis were randomly allocated to either Seatone (green-lipped mussel extract) or placebo in order to assess the former's claimed effectiveness in rheumatoid disease. After six months there was no significant improvement in any laboratory or clinical measurement of disease activity in the Seatone group. The patients on active drug fared no better than those on placebo. These results suggest that Seatone is not effective in rheumatoid arthritis.